Effect of a tailored upper extremity strength training intervention combined with direct current stimulation in chronic stroke survivors: A Randomized Controlled Trial - Palimeris, Stephania; Ansari, Yekta; Remaud, Anthony; Tremblay, François; Corriveau, Hélène; Boudrias, Marie Hélène; Milot, Marie Hélène (Frontiers in Rehabilitation Sciences, 2022)
Strengthening exercises are recommended for managing persisting upper limb (UL) weakness following a stroke. Yet, strengthening exercises often lead to variable gains because of their generic nature. For this randomized controlled trial (RCT), we aimed to determine whether tailoring strengthening exercises using a biomarker of corticospinal integrity, as reflected in the amplitude of motor evoked potentials (MEPs) elicited by transcranial magnetic stimulation (TMS), could optimize training effects in the affected UL. A secondary aim was to determine whether applying anodal transcranial direct current stimulation (tDCS) could enhance exercise-induced training effects. For this multisite RCT, 90 adults at the chronic stage after stroke (>6 months) were recruited. Before training, participants underwent TMS to detect the presence of MEPs in the affected hand. The MEP amplitude was used to stratify participants into three training groups: 1) low-intensity, MEP<50 μV, 2) moderate-intensity, 50 μV 120 μV. Each group trained at a specific intensity based on the one-repetition maximum (1 RM): low-intensity, 35-50% 1RM; moderate-intensity, 50-65% 1RM; high-intensity, 70-85% 1RM. The strength training targeted the affected UL and was delivered 3X/week for four consecutive weeks. In each training group, participants were randomly assigned to receive either real or sham anodal tDCS (2 mA, 20 minutes) over the primary motor area of the affected hemisphere. Pre/post-intervention, participants underwent a clinical evaluation of their UL to evaluate motor impairments (Fugl-Meyer Assessment), manual dexterity (Box and Blocks test) and grip strength. Post-intervention, all groups exhibited similar gains in terms of reduced impairments, improved dexterity, and grip strength, which was confirmed by multivariate and univariate analyses. However, no effect of interaction was found for tDCS or training group, indicating that tDCS had no significant impact on outcomes post-intervention. Collectively, these results indicate that adjusting training intensity based on the size of MEPs in the affected extremity provides a useful approach to optimize responses to strengthening exercises in chronic stroke survivors. Also, the lack of add-on effects of tDCS applied to the lesioned hemisphere on exercise-induced improvements in the affected UL raises questions about the relevance of combining such interventions in stroke.